Fase-fase Perkembangan Manusia dalam Islam dan Relevansinya Terhadap Pemikiran Muhammad Izzuddin Taufiq: The Phases of Human Development in Islam and Their Relevance to the Thought of Muhammad Izzuddin Taufiq - Mukhlis, Mukhlis (JURNAL TILA ( Tarbiyah Islamiyah Lil Athfaal ), 2022)
This research describes the phases of human growth and development according to Islam and the views of Muhammad Izzuddin in his work on the Qur'an and Embryology. To obtain superior investment in children, it is necessary to pay attention to the education and development of children from the womb. Because the period in the womb is the basis for further development. This type of research is a literature review which takes the stages of reading, reviewing and recording various literature or reading materials that are appropriate to the subject matter, then filtered and set forth in a theoretical framework. The results of this study indicate that Islam explains human life has begun before birth. Humans have a spirit that has lived before the time of his birth in the world. On a day called mistaq day, all human souls gather to give testimony acknowledging the oneness and divinity of Allah. The Qur'an posits that humans were basically created from soil, then in the next creation process from the mixing of male sperm and female ovum originating from the essence of the soil. Judging from the stages of its development, it consists of several phases, namely: 1) Soil extract stage, 2) Semen stage, 3) Germ stage (meeting of male sperm and female ovum), 4) Alaqah stage, 5) Mudgha stage, 6) Stage izhama, 7) Lahman stage, 8) Khalqan akhar stage. Broadly divided into four global periods, namely, the nutfah period of forty days, the alaqah period of approximately forty days, the mudghah period also lasts approximately forty days, and the period of the fetus or the development of the mudghah which is given a spirit.